PENGEMBANGAN MEDIA BUKU SAKU PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SEKOLAH DASAR NEGERI 111 KOTA JAMBI - Filma Kumala Sari; Puspita Sari; Usi Lanita; Fajrina Hidayati (Jurnal Multidisipliner Bharasumba, 2026)
Practicing Clean and Healthy Living Behavior (PHBS) plays a crucial role effort to improve the health status of elementary school–aged children. However, the implementation of PHBS at Public Elementary School 111, Jambi City, is still relatively low, partly due to the limited availability of educational media that are attractive and easy for students to understand. This study aimed to develop PHBS educational media in the form of a pocket book and to analyze its feasibility as a health learning medium. This study utilized a Research and Development (R&D) approach following the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. During the development process, the product was validated by media experts, language experts, health promotion experts, and an institutional validator, as well as 19 fourth- and fifth-grade students of Public Elementary School 111 Jambi as participants. The results showed that the PHBS pocket book was considered feasible for use as a health education medium in elementary schools. This pocket book media is expected to increase students’ knowledge and awareness in implementing PHBS in the school environment.